(untitled) (Fiep Bulletin - online, 2012)
This article results from a research project and extension-related workshops that includestretching of all members of the body, tai chi, aerobics and lian gong, offered to elderly patients in the Family Health Program - PSF, in San Jose neighborhood and the Center for Reference and Social Care - CRAS, both located in the municipality of Santana doIpanema - AL. Initially, we performed semi-structured interviews with a history and physical assessment in all cases, where it was identified that these elderly maintained a sedentary lifestyle and had more health problems. The project has been ongoing since November2010, serving two classes, at different times, three times a week. The results of this projecthave shown the importance of physical activity, since it has contributed to the weight reduction, reduction of pain in the legs and spine, and especially with the increasedpsychosocial health, because these meetings and the friendships that were made as well as the distraction before, during and after is very large, it is known to change in habits, such as clothing, food and others who come to work directly with the promotion of health that is our primary goal.